The Use of Text Based-Media Application Folklore To Improve Student’s Vocabulary - Maria Aciana Jehanut; Abdul Rohman; Widi Syahtia Pane (Wadah Inovasi Indonesia, 2023)
Background: Learning vocabulary to increase vocabulary acquisition among students, teachers should continuously come up with engaging lesson plans and methods that they know will resonate with their students. The strategy employed will have a significant impact on how much fun studying and learning in class can be had. One technique that will be employed is folklore. Folklore is a kind of oral tradition that, because of its many defining features, is both simpler and more straightforward to comprehend than other forms of literature. Methodology: This researcher is a classroom action researcher This study addressed a four-part cycle and offered solutions to the queries raised in class. Observation, evaluation of test findings, and documentation were used to gather the data. Findings: The results of this study showed an increase in students’ vocabulary data obtained by the researcher from pre-test and post-test scores that the usage of short stories in the classroom had improved and they were learning. When attempting to expand participants' vocabulary, it's an excellent idea to employ short stories as lesson plans and teach tricks. Conclusion: This conclusion can be supported by the average pre-test score of students' skills, which was 46.91 in the first and last managed to attract but grew to 80.20 in cycle I. Therefore, the pre-test for the students' cycle I vocabulary evaluation was deemed appropriate. Folklore may be a very efficient teaching method and strategy, especially in vocabulary. This is based on the fact that folklore engages students in educational activities and appears to offer motivation through moral teachings. Originality: Folklore is a rich source of knowledge that may be applied to much more than just learning new words. Using folklore as a learning tool is an alternative to the traditional techniques for teaching English vocabulary